(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Given the accepted axiom about the potential danger of any human activity, we can conclude that it is impossible that there is no danger. The task of “risk analysis” in any production is to determine the minimum (permissible) values for various hazardous and harmful production factors and the appropriate maximum costs to achieve them.